Analisis Citraan dalam Kumpulan Puisi Kamu Tidak Istimewa Karya Natasha Rizky - Kariyani, Syahiral; Khalid, Idham; Riadi, Selamet (Universitas Qamarul Huda Badaruddin, 2023)
: This study aims to describe the forms of imagery found in Natasha Rizky's poetry collection Kamu Tidak Istimewa and analyze how these images influence readers' thoughts, feelings, and emotions. The research employed a descriptive qualitative method using close reading of 30 selected poems out of 59 in the collection. The findings revealed a predominance of intellectual imagery (24 instances), followed by visual imagery (12), auditory imagery (12), kinesthetic imagery (12), tactile imagery (5), and both olfactory and gustatory imagery with only 2 instances each. These results highlight the poet's diverse use of imagery to construct emotional nuances, strengthen meaning, and foster readers' reflection on themes of love, loss, and identity. This study contributes to literary appreciation studies, particularly imagery analysis in poetry.